Role of Gut Microbiota in the Pharmacological Effects of Natural Products - Pan, Chuyue; Guo, Qinglong; Lu, Na (Evidence-Based Complementary and Alternative Medicine, 2019)
Increasing evidence has demonstrated that natural products derived from traditional Chinese medicine, such as ginseng, berberine, and curcumin, possess a wide variety of biological activities on gut microbiota, which may cause changes in the composition of intestinal microbiota, microbial metabolites, intestinal tight junction structure, and mucosal immunology. These changes will eventually result in the exertion of the pharmacological effects by treatment with these natural products. In this review, we will discuss how gut microbiota is influenced by commonly used natural products. Furthermore, our findings are expected to provide novel insight into how these untargeted natural products function via gut microbiota.